2023
DOI: 10.1073/pnas.2310067120
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the nonhelical filament of the Alzheimer’s disease tau core

Pu Duan,
Aurelio J. Dregni,
Nadia El Mammeri
et al.

Abstract: The microtubule-associated protein tau aggregates into neurofibrillary tangles in Alzheimer’s disease (AD). The main type of aggregates, the paired helical filaments (PHF), incorporate about 20% of the full-length protein into the rigid core. Recently, cryo-electron microscopy data showed that a protease-resistant fragment of tau (residues 297–391) self-assembles in vitro in the presence of divalent cations to form twisted filaments whose molecular structure resembles that of AD PHF tau [S. Lövestam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…It is also worth noting that the concentration of the protein is important in determining the type of structure formed. Recent Cryo-EM and solid-state NMR studies suggest that tau 297–391 construct can form filaments with nonhelical structures, distinct from those found in Alzheimer’s disease when incubated with MgCl 2 . , However, the cryo-EM study showed that only when 2 mg/mL of protein was employed, around 90% of filamentous structures resembling PHF associated with Alzheimer’s disease (AD) were obtained, while higher concentration of protein produces fibrils which are dissimilar to ex vivo AD filaments . Therefore, in our study, we used ∼2 mg/mL (250 μM) protein for all experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worth noting that the concentration of the protein is important in determining the type of structure formed. Recent Cryo-EM and solid-state NMR studies suggest that tau 297–391 construct can form filaments with nonhelical structures, distinct from those found in Alzheimer’s disease when incubated with MgCl 2 . , However, the cryo-EM study showed that only when 2 mg/mL of protein was employed, around 90% of filamentous structures resembling PHF associated with Alzheimer’s disease (AD) were obtained, while higher concentration of protein produces fibrils which are dissimilar to ex vivo AD filaments . Therefore, in our study, we used ∼2 mg/mL (250 μM) protein for all experiments.…”
Section: Resultsmentioning
confidence: 99%